PERAN MARKETPLACE DALAM MEMBERIKAN PERLINDUNGAN TERHADAP KONSUMEN MENURUT UNDANG-UNDANG PERLINDUNGAN KONSUMEN - SAPUTRA, HENDRA ADI (Universitas Mahasaraswati K. Mataram, 2023)
The Consumer Protection Law mandates that consumers must be protected both before using the product and after using the product. In protecting themselves, consumers have limits, therefore the role of the marketplace as a business actor is needed in online buying and selling because the marketplace is a service provider or platform that facilitates sellers and consumers in transactions. What is the role of the marketplace in providing protection to consumers according to the Consumer Protection Law in Indonesia? Using normative research methods, it was found that in Law Number 8 of 1999 concerning Consumer Protection, Articles 6 to Article 27 explain the responsibilities of business actors towards consumers, as business actors are marketplaces (platform service providers) can make policies towards sellers without offering merchandise prohibited by UUPK on its platform. Marketplaces can provide consumer complaint facilities on their platforms so that consumers can choose trustworthy sellers and avoid rogue sellers.